2016
DOI: 10.1002/14651858.cd003091.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Dressings for the prevention of surgical site infection

Abstract: Background Surgical wounds (incisions) heal by primary intention when the wound edges are brought together and secured, often with sutures, staples, or clips. Wound dressings applied after wound closure may provide physical support, protection and absorb exudate. There are many different types of wound dressings available and wounds can also be left uncovered (exposed). Surgical site infection (SSI) is a common complication of wounds and this may be associated with using (or not using) dressings, or different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(102 citation statements)
references
References 78 publications
1
89
0
12
Order By: Relevance
“…There is great need for a new approach to develop a post-surgical dressing that reduces the risk of surgical site infections. Current meta-analysis provides no evidence that current products reduce the risk of surgical site infections (50). As only primates and humans have cathelicidin antimicrobial peptide gene, our future work will be focusing on validation of these fiber formulations in a humanized transgenic mouse model or clinical trial testing by comparing systemic administration to localized delivery techniques.…”
Section: Discussionmentioning
confidence: 99%
“…There is great need for a new approach to develop a post-surgical dressing that reduces the risk of surgical site infections. Current meta-analysis provides no evidence that current products reduce the risk of surgical site infections (50). As only primates and humans have cathelicidin antimicrobial peptide gene, our future work will be focusing on validation of these fiber formulations in a humanized transgenic mouse model or clinical trial testing by comparing systemic administration to localized delivery techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The United Kingdom NICE, in a publication on surgical site infection, 17 highlighted the gap in published evidence on the use of alternate wound dressings for incisional surgical wounds 22-25 and suggested that chronic wound dressings could be used for surgical incisions to minimise the risk of SSI.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, a case for prolonged postoperative treatment in pigs could be made on the basis that contamination levels in the animal's recovery environment are likely to be greater than those found in a postoperative ward. Evidence that prolonged antimicrobial administration does not reduce SSIs and that integumentary integrity and local immune competency are probably more important than environmental isolation (Dumville and others 2011) mitigates against this.…”
Section: Discussionmentioning
confidence: 99%